Evaluating The Adoption The Use Of Green Technology And Sustainability Design For Buildings In Penang - Mohamad Zaidi, Mohamad Irfan (2019)
The main purpose of this research is to study and evaluate the adoption of the use of green building technology and sustainability design in terms of priority, requirements and preferences in relation to the public’s requirements in Penang. The main objective of this research is to evaluate the adoption of the use of green technology and sustainability design for buildings in Penang. The goal is to identify the priority and preference of building design according to the public in Malaysia so the it can be used to propose to local architects, contractors and developers about the effectiveness of green technology. The data gathered for this research was collected using various instruments such as literature review and survey questions. The questionnaire papers are distributed to the sample population, recollected and analysed using the SPSS software to obtain the results. The results show that most people expressed a positive respond to the concept of green technology. However, most respondent are not well aware and fully understand the concept itself. Accordingly, the research was conducted and the discoveries of this research are expected to assist future building owners and developers to fully comprehend the concept of green building technology and design preferences. Hopefully, this will meet with the public’s requirements and preferences.